Ensaio não destrutivo baseado em medidas de campo magnético para acompanhamento da formação da fase sigma em um aço inoxidável duplex - Fialho, Walter Macêdo Lins (2015)
Duplex stainless steels (AID) are characterized for having good mechanical strength and corrosion. However, when subjected to manufacturing processes requiring the material thermal cycles with temperatures above 600 ° C, occurs emergence of fragile phases that compromise his toughness and corrosion resistance. Among these phases there is the presence of σ phase, rich in chromium and high hardness. In this paper we sought to develop a monitoring technique of the formation of σ phase. This technique is based on the study of the interaction between microstructure of the duplex stainless steel and the magnetic field applied to the material. Specimen with different amounts of σ phase were obtained by aging at temperatures of 800 °C and 900 °C. Aged AID was characterized by optical microscopy and scanning electron, hardness tests, impact tests and X-ray diffraction. The volumetric percentage of this phase was estimated by X-ray diffraction and processing of optical microscopy images. The magnetic field measurements were performed with a Hall effect sensor. The results show that the rise of the phase reduced the σ value of the magnetic permeability of the material, indicating that the magnetic properties and permeability measurements, as well as the resultant magnetic field, can be used for monitoring formation of this phase. The study proves to be developed effective technique for monitoring the duplex stainless steel embrittlement.